1993
DOI: 10.1093/jaoac/76.4.703
|View full text |Cite
|
Sign up to set email alerts
|

Total Organochlorine Content of Fish from the Great Lakes

Abstract: Residues of polychlorinated biphenyls (PCBs) and organochlorine pesticides were determined in several species of commercial fish from the Great Lakes and compared to the total organic chlorine determined by neutron activation analysis. The mean organochlorine contents ranged from 44 to 138 ppm (lipid basis) and were 5 to 72 times higher than the contents of PCBs and organochlorine pesticides. Marine fish also contained a large proportion of unidentified organic chlorine. The unknown material in the Great Lakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…On a lipid weight basis, Atlantic croaker contained the highest EOCl concentrations, whereas yellow tail had the least. The concentrations of EOCl found in fish samples were at least 10-fold greater than those reported for fishes from the Great Lakes (22) and carp from the Buffalo River, NY (15).…”
Section: Resultscontrasting
confidence: 56%
“…On a lipid weight basis, Atlantic croaker contained the highest EOCl concentrations, whereas yellow tail had the least. The concentrations of EOCl found in fish samples were at least 10-fold greater than those reported for fishes from the Great Lakes (22) and carp from the Buffalo River, NY (15).…”
Section: Resultscontrasting
confidence: 56%
“…Similar to our results, Gustavson and Mar (1999) reported that PCB contributed to less than 1.3 to 21% of EPOCl in surface sediment, and that PCB, HCH, and DDT contributed to less than 0.2 to 19% of EPOCl in blue mussels from the Baltic Sea. Other reports showed that 74 to 99% of extractable organochlorines in several species of fish (Newsome et al, 1993) and 80.6 to 98.6% of EPOCl in pine needles from China (Xu et al, 2003) could not be accounted for by PCB and OCP.…”
Section: Epocl In 18 Chinese Commercial Yogurt Samplesmentioning
confidence: 92%
“…Therefore, PCB concentrations are usually reported as total PCBs, which is determined by the sum of the peaks in the sample that match peaks found in an Aroclor mixture. Numerous studies have examined the total PCB concentrations found in Great Lakes fish [1–6]. Although this approach may be beneficial with respect to environmental monitoring, it offers little information regarding the individual congeners that comprise the total PCB concentration.…”
Section: Introductionmentioning
confidence: 99%